2020
DOI: 10.2166/wpt.2020.007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sidestream dewatering liquors from thermally hydrolised and anaerobically digested biosolids

Abstract: A long term operation (22 months) of the sidestream treatment plant at the water and resource recovery facility at the Tilburg sewage works in The Netherlands is presented. This plant treats dewatering reject liquor from thermally hydrolysed (THP) and mesophillic anaerobically digested (MAD) biosolids. The sidestream plant is comprised of a Phospaq struvite reactor for removal and recovery of phosphate and an Anammox reactor for removal of ammoniacal nitrogen. Potential inhibiting characteristics of THP-MAD re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Previous studies reported a reduction of AOB activity by 40-60% AOB in THP/AD [5,6], but the same was not observed in this study. Our results align with the reports by Driessen et al (2020) [7] who demonstrated successful nitrogen removal with a granular sludge deammonification process from THP/AD dewatering liquors (NRR 1.0-2.0 kg N m −3 d −1 ). Hence, this study provides additional evidence that deammonification can be used as a nitrogen removal process for ammonia from THP/AD dewatering liquors and concerns about inhibition must be further investigated on a case-by-case basis.…”
Section: Figure 2 (A)supporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported a reduction of AOB activity by 40-60% AOB in THP/AD [5,6], but the same was not observed in this study. Our results align with the reports by Driessen et al (2020) [7] who demonstrated successful nitrogen removal with a granular sludge deammonification process from THP/AD dewatering liquors (NRR 1.0-2.0 kg N m −3 d −1 ). Hence, this study provides additional evidence that deammonification can be used as a nitrogen removal process for ammonia from THP/AD dewatering liquors and concerns about inhibition must be further investigated on a case-by-case basis.…”
Section: Figure 2 (A)supporting
confidence: 92%
“…The inhibition of THP/AD dewatering liquors has been associated with parts of the particulate and colloidal chemical oxygen demand (COD) that decreased AOB and AMX activity [6]. However, some recent studies found that deammonification technologies removed ammonia from THP/AD dewatering liquors efficiently, according to their design load and removal without displaying inhibition [7,8]. Many full-scale suspended sludge deammonification technologies operate at nitrogen loading rates (NLR) of 0.3-0.8 kg N m −3 d −1 with conventional AD dewatering liquors while displaying of 85-90% [9].…”
Section: Introductionmentioning
confidence: 99%
“…This property has been hypothesized to be one of the mechanisms by which melanoidins have anti-microbial properties with the ability to inhibit growth of pathogenic organisms (Morales et al, 2005). However, on a treatment plant, these chelating properties have been found to render supplemental micronutrients added to a deammonification sidestream plant (treating liquors from thermal hydrolysis and digestion) ineffective (Driessen et al, 2018).…”
Section: Properties and Types Of Colored Refractory Compoundsmentioning
confidence: 99%
“…The authors concluded that phosphate produced during digestion was a consequence of polyphosphate hydrolysis. Due to increased sludge concentration and solubilization, phosphorous recovery appears to be a complementary with thermal hydrolysis and digestion, and has recently been gaining traction (Driessen et al, 2018;Taylor, 2019).…”
Section: Phosphorousmentioning
confidence: 99%
“…However, when total nitrogen removal is required, these systems become attractive due to lower operating costs than traditional activate sludge treatment, due largely to the savings from carbon (e.g., methanol) supplementation. Deammonification systems need the digestate to be diluted with water by a ratio of 1-1.5 units of water per unit of digestate treated to overcome heterotrophic interference (Driessen et al, 2018;de Clippeleir et al, 2019). Alternatively, deammonification systems may have pre-treatment to remove COD and suspended solids.…”
Section: Treatment Of Return Liquorsmentioning
confidence: 99%